Dynamic rupture scenarios in the Brawley Seismic Zone, Salton Trough, southern California - Meltzner, Aron Jeffrey (2019)
In this paper we investigate the dynamic behavior of a system of interconnected faults in the Brawley Seismic Zone (BSZ) in southern California. The system of faults includes the southern San Andreas Fault (SSAF), the Imperial Fault (IF), and a set of cross faults in the BSZ that may serve as connecting structures between the two larger faults. Geological and seismic evidence imply that the SSAF and IF may have buried extensions that link them together in a large‐scale step over, with the cross faults in the BSZ cutting between them. Such a configuration poses the question of whether through‐going rupture across the step over is possible in this region, leading to large, plate‐boundary scale earthquakes. We investigate potential earthquakes in this region through 3‐D dynamic finite element spontaneous rupture modeling. We find that under multiple assumptions about fault stress and fault geometry, through‐going rupture is possible, both from north to south and south to north. Participation of the cross faults is facilitated by two factors: absence of rupture on one of the main two faults and a contrast in prestress between the main faults and the cross faults, leading to slow propagation speed on the main faults while maintaining ease of failure on the cross faults. The pattern of rupture propagation and slip is strongly affected by fault‐to‐fault dynamic stress interactions during the rupture process. The results may have implications for both potential earthquakes in this region, as well as for understanding the dynamics of geometrically complex/branched faults in general.